Elementary Processes in Organic Photovoltaics - Leo, Karl (Springer International Publishing : Imprint: Springer, 2017)
This volume presents the results of a multi-year research programme funded by the Deutsche Forschungsgemeinschaft (German Research Council), which explains how organic solar cells work. In this new promising photovoltaic technology, carbon-based materials are deposited by low-cost methods onto flexible substrates, thus allowing devices which open completely new applications like transparent coatings for building, solar cells integrated into clothing or packages, and many more. The investigation of organic solar cells is an interdisciplinary topic, covering physics, chemistry and engineering. The different chapters address topics ranging from the synthesis of new organic materials, to the characterization of the elementary processes such as exciton transport and separation, and the principles of highly efficient device design.- Resumé vydavatel
Keywords: fotovoltaické články; organická chemie; fotoelektrické články; photovoltaic elements; organic chemistry; photoelectric cells; elektronické knihy; sborníky; electronic books; papers of several authors